Analisis Kuat Geser Tanah Lempung menggunakan Kapur dan Petrasoil - Indrayani Indrayani . (Jurnal Teknologi Terpadu, 2020)
Several studies have added lime, fly ash, or gypsum to clay soils to increase the shear strength of relatively low clay soils. The addition of lime and petrasoil as solvents in water was carried out in this study, where petrsoil is often used in Indonesian road construction works. This study aims to obtain the effect of adding lime and petrasoil to the shear strength of clay. The tests consists of the index properties, seive analysis, atterberg limits, soil compaction, and shear strength testing, based on SNI and ASTM. Mixed variations consist of 6, namely: (i) soil + petrasoil; (ii) soil + 10% lime + petrasoil; (iii) soil + 15% lime + petrasoil; (iv) soil + 20% lime + petrasoil; (v) soil + 10% lime + water; (vi) soil + water; all variations without ripening. The test results showed an increase in the value of soil cohesion in the addition of petrasoil and lime variations of 20%, amounting to 50.94. While the angle of shear of the soil increased with the addition of lime at a variation of 10% both with water and with petrasoil, which amounted to 35.10. This shows an increase in soil shear strength with the addition of petrasoil and lime to the soil.